The new Laender as an industry location in unified Germany - Thiess Büttner (Universität Konstanz, Forschungsschwerpunkt Internationale Arbeitsmarktforschung, 1994)
This paper discusses whether the dominant position of the Old Laender's economy in the unified Germany hampers the reemergence of industrial production in the New Laender. For that purpose productivity differences are explained by specialization advantages of industrial agglomerations, which are localized by transport costs. The industrial locations are endogenized in a model with trade, migration and also interregional firm location. To point out the relationship of the theoretical argument to the conditions in unified Germany the roles of transport costs, trade in intermediates, congestion effects, start-up costs, and knowledge spillovers are discussed. Although the influence of the agglomerative forces can not be rejected, a persistent deindustrialization of the New-Laender is found difficult to project.
Keywords: 330; Produktionsstandort; Neue Bundesländer